PENGARUH PELATIHAN DAN PEMBINAAN TERHADAP PENGEMBANGAN USAHA KECIL PADA PROGRAM KEMITRAAN BINA LINGKUNGAN - Raden Rudi Alhempi; Wismar Harianto (Universitas Trisakti, 2013)
One company has been paying attention to small business development is PT. Telkom Pekanbaru Branch through its Community Development Centre (CDC) to run the Partnership Program and Community Development (CSR) by providing financial assistance as well as nonfinancial assistance such as training and coaching for small business. However, performance of partners in making repayment of loans granted by the CDC PT. Telkom Pekanbaru Branch is still high. This study aims to determine the effect of training and coaching to small business development in the Community Development Partnership Program (CSR) by the Community Development Centre PT Telkom Pekanbaru Branch. The study population is all of which amounts to 277 people with a sample of 73 people Data from this study are primary data using questionnaires as research instruments. Data analysis techniques that used in this research is descriptive and inferential statistical analysis using SPSS. The result show that training and coaching jointly or individually have a significant influence on the development of small business. Coaching is a variable that has the highest donation or the value of job satisfaction in small business.Keywords: Training, Coaching, Small business development, Community development centre (CDC)